The Effect of Adversity Quotient and Family Environment on Entrepreneurial Intention on Faculty of Economics of Jakarta State University - Nafisah, Afi Nur; Zulaihati, Sri; Mardi, Mardi (First Ciera Publisher, 2023)
This research aims to determine the influence of Adversity Intelligence and Family Environment on Entrepreneurial Interest in Undergraduate Students at the Faculty of Economics, Jakarta State University. The population of this study was 417 undergraduate students at the Faculty of Economics, Jakarta State University, Class of 2021. From the total research population, 211 students were taken as samples using the calculation technique, namely Slovin. In this study, researchers used research instruments with quantitative methods with a total of 211 respondents. Data collection was carried out by distributing questionnaires with proportional random sampling. The research was conducted using the SPSS version 25 application. The results of this research show that 1) Adversity Intelligence has a positive and significant influence on Entrepreneurial Interest; 2) Family environment has a positive and significant influence on entrepreneurial interest. The variables used in this research are still relatively small, so they can be added with other variables such as Entrepreneurship Education, Self-Efficacy, Learning Outcomes and Locus of Control. It can also be said that the sample in this study cannot represent all students at the Faculty of Economics, Jakarta State University because it only examined students from the Class of 2021.